Trypanosoma Infection Rates in Glossina Species in Mtito Andei Division, Makueni County, Kenya - Daniel Mutiso Nthiwa; David O. Odongo; Horace Ochanda; Samoel Khamadi; Bernard M. Gichimu (Journal of Parasitology Research)
African Animal Trypanosomiasis (AAT) transmitted cyclically by tsetse fly (Glossina spp.) is a major obstacle to livestock production in the tropical parts of Africa. The objective of this study was to determine the infection rates of trypanosomes in Glossina species in Mtito Andei Division, Makueni County, Kenya. Tsetse fly species, G. longipennis and G. pallidipes, were trapped and DNA was isolated from their dissected internal organs (proboscis, salivary glands, and midguts). The DNA was then subjected to a nested PCR assay using internal transcribed spacer primers and individual trypanosome species were identified following agarose gel electrophoresis. Out of the 117 flies trapped in the area 39 (33.3%) were teneral while 78 (67%) were nonteneral. G. pallidipes constituted the largest percentage of 58% while G. longipennis were 42%. The overall trypanosomes infection rate in all nonteneral Glossina spp. was 11.53% with G. longipennis recording the highest infection rate of 23.08% while G. pallidipes had an infection rate of 5.77%. T. vivax was the most infectious (10.26%) compared to T. congolense (1.28%). Mean apparent densities were strongly positively correlated with infection rates (r=0.95) confirming the importance of this parameter as an indicator of AAT transmission risk.